Using a journal to engage teachers in developmental work - Emanuelsson , Göran; Johansson, Bengt; Reys, Barbara J.; Reys, Robert E. (NOMAD Nordic Studies in Mathematics Education, 1996)
Professional journals provide a fresh and stimulating source of ideas and serve as both a lifeline and a conduit for professional growth for many teachers. Journals have the potential to address timely issues and reach teachers regularly. Furthermore, journals represent a significant resource to promote dialogue about teaching and learning as well as to chronicle historical developments within professional fields. This article details how a Swedish journal for mathematics teachers, Nämnaren, was used to focus on a timely issue and stimulate awareness and involvement of mathematics teachers throughout the country. Nämnaren was founded over 20 years ago and established with the stated purpose of helping Swedish teachers: keep informed of current issues and happenings in mathematics education; and learn more effective ways to learn and teach mathematics at all levels. Nämnaren is published four times a year and has a circulation that reaches nearly all elementary and secondary schools in Sweden. Several issues of Nämnaren were used recently to bring the mathematical theme of number sense to the attention of Swedish teachers *).